2013
DOI: 10.4238/2013.april.17.5
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation involved in proline accumulation in response to osmotic stress in rice (Oryza sativa)

Abstract: ABSTRACT. Proline accumulation is involved in plant osmotic stress tolerance. Given that DNA methylation is related to almost all metabolic processes through regulation of gene expression, we suspected that this epigenetic modification and proline biosynthesis are probably related. To test this, we investigated whether osmotic stress-induced proline accumulation is associated with DNA methylation modifications in rice. We assessed DNA methylation and expression of 3 key genes (P5CR, P5CS, and δ-OAT) involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 28 publications
4
33
0
1
Order By: Relevance
“…This is a well-known response of these genes to salinity stress (Szabados and Savouré, 2009). The results we report here about epigenetic changes affecting P5CS1 gene in a context of salinity stress are in agreement with data published by Zhang et al (2013) regarding the response of rice to osmotic stress, obtained with a low-resolution technique for methylation analysis.…”
Section: Discussionsupporting
confidence: 94%
“…This is a well-known response of these genes to salinity stress (Szabados and Savouré, 2009). The results we report here about epigenetic changes affecting P5CS1 gene in a context of salinity stress are in agreement with data published by Zhang et al (2013) regarding the response of rice to osmotic stress, obtained with a low-resolution technique for methylation analysis.…”
Section: Discussionsupporting
confidence: 94%
“…The nonrandomness of the change was validated by a housekeeping gene used as a control. The demethylation of P5CS and δ-OAT and their consequent upregulation contributed to the enhanced Pro synthesis and accumulation (Zhang et al, 2013). More significantly, most of these stress-induced epigenetic modifications are reset to the basal level once the stress is relieved, but some of the modifications may be stable, i.e.…”
Section: Changes In Dna Methylation Pattern Governs Pro Accumulationmentioning
confidence: 99%
“…However, the studies on long-term stress memory within generation, as well as transgenerational stress memory of proline accumulation and the underlying regulatory mechanisms, are just starting to emerge in the context of rapid progress in plant epigenetic research. It has recently been reported that pretreatment of Arabidopsis with menadione sodium bisulphite could induce more rapid and higher proline accumulation upon subsequent salt stress, which was associated with a hypomethylation state at the promoter region of P5CS1 and proline dehydrogenase 1 (PDH1) (3). In rice, the progenies of osmotically stressed plants were found to acquire altered DNA demethylation in P5CS1 and ornithine-δ-animotransferase (δ-OAT), but not in pyrroline-5-carboxylate reductase (P5CR), correlated with the inheritable up-regulation of P5CS1 and δ-OAT and elevated proline accumulation (3,4).…”
mentioning
confidence: 99%
“…It has recently been reported that pretreatment of Arabidopsis with menadione sodium bisulphite could induce more rapid and higher proline accumulation upon subsequent salt stress, which was associated with a hypomethylation state at the promoter region of P5CS1 and proline dehydrogenase 1 (PDH1) (3). In rice, the progenies of osmotically stressed plants were found to acquire altered DNA demethylation in P5CS1 and ornithine-δ-animotransferase (δ-OAT), but not in pyrroline-5-carboxylate reductase (P5CR), correlated with the inheritable up-regulation of P5CS1 and δ-OAT and elevated proline accumulation (3,4). However, the effect of histone modification on the memory response of proline accumulation upon stress has not been investigated.…”
mentioning
confidence: 99%